159k views
3 votes
Solve the equation for x

z=m+x-y a)x=-z+m+y b)x=z-m+y c)x=z+m-y d)x=z+y+m

User ChaoS Adm
by
5.1k points

1 Answer

4 votes

Answer:

x = z - m + y

Explanation:

Given:


\displaystyle \large{z = m+x-y}

To solve for x-term, we have to isolate it. We can do by subtracting m-term both sides and add y-term both sides.


\displaystyle \large{z-m+y=m+x-y-m+y}\\\\\displaystyle \large{z-m+y=x}\\\\\displaystyle \large{x=z-m+y}

Therefore, the answer to this question is x = z - m + y

Please let me know if you have any questions regarding my answer or explanation!

User Farseer
by
5.8k points